Template-asisted visible light-induced [2+2] photodimerization in a pseudopolymorphic binary solid: topotactic transformation vs photoinduced crystal melting - Ahsan, Mollah Rohan; Varma, Harshit; Mishra, Manish Kumar; Mukherjee, Arijit (CRYSTAL GROWTH & DESIGN, 2024)
Keywords: CATION-PI INTERACTIONS; SINGLE-CRYSTAL; STATE PHOTODIMERIZATION; Supramolecular

Photo-induced cracking in a Bi-component molecular solid: capturing structural intermediates - Ahsan, Mollah Rohan; Mishra, Manish Kumar; Mukherjee, Arijit (Chemistry-An Asian Journal, 2025)
A photo-responsive bi-component solid is designed based on robust large synthons. The study not only provides a template-based approach for a system that was difficult to photo-dimerize, but the designed solid also leads to photo-induced cracking upon photodimerization. The delicate structural design helps in capturing the structural intermediates, which reveals a possible reorientation of the photodimer within the crystal to maintain structural integrity.
Keywords: bi-component solid; crystal engineering; photoinduced cracking; single-crystal-to-single crystal transformation; [2+2] photodimerization